К вопросу создания математической модели виброабразивной обработки деталей на вибрирующем держателе в неподвижном контейнере - Бранспиз, Е. В.; Калмыков, М. А.; Нечай, Е. В. (Eastern-European Journal of Enterprise Technologies, 2009)
The article is devoted to the development of mathematical model, which describing the processes, which happenings on finishing operations of detail’s treatment, with the use of vibroarbor method, where the vertical moving of spindle is set an arbor for providing the uniform processing on vertical dimension in immobile container,which contains a polishing abrasive, being in the free state